Revisiting Curriculum Approaches and Operational Designs in Islamic Boarding Schools for Student Readiness in the Industrial Revolution 4.0 Era - Supratama, Riky; Wahyuni, Dina Auliatil; Layalin, Nurhuda Alfina; Hidayat, Riyan (PT Mutiara Bustan Ilmu, 2025)
This study aims to analyze the operational curriculum of Islamic boarding schools in dealing with the needs of students in the era of the Industrial Revolution 4.0, with a focus on the approach and design of the curriculum. In the context of Islamic boarding schools, the use of information technology is still limited, so it is necessary to rearrange the curriculum to adapt to the challenges of the evolving times. This study raises questions about the challenges of pesantren in facing the needs of students in the era of the Industrial Revolution 4.0, the suitability of the approach of the pesantren operational curriculum to the needs of students, and the suitability of the design of the pesantren operational curriculum with the needs of students in the era of the Industrial Revolution 4.0. The research method used is qualitative with a library research approach. The results of the analysis are expected to provide an overview of the quality of the pesantren curriculum in facing the challenges of the ever-evolving times. This research is expected to contribute to improving the quality of pesantren education in the era of the Industrial Revolution 4.0.